Politics and value in English studies a discipline in crisis? - Guy, Josephine M. 1963- (Cambridge University Press, 1993)
The current debate about the nature of English studies has questioned the status of English as a discipline. In this 1993 book, Josephine Guy and Ian Small set this so-called 'crisis in English' within the larger context of disciplinary knowledge. They examine the teaching of English and literary studies in the United States and Britain, and argue that the explicit attempt by some radical critics on both sides of the Atlantic to politicise the discipline has profound consequences for the nature of English studies. They describe the state of disciplinary knowledge, together with its social and philosophical preconditions; they analyse proposals for reform; and they discuss the ways in which these proposed reforms would affect the three main practices of the discipline - literary criticism, literary history and text-editing. In the process they demystify issues and arguments which have often in the past been obscured by jargon and polemic
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Politik; English philology / Study and teaching / Great Britain; English philology / Study and teaching / Political aspects / Great Britain; English literature / History and criticism / Theory, etc; Politics and literature / Great Britain; Anglistik; Wertorientierung; Theorie; Krise; Englisch; Politische Bildung; Wert; Literaturwissenschaft; Großbritannien; USA